Effect of annealing treatments on the mechanical behaviour of UHTCMCs prepared by mild polymer infiltration and pyrolysis. Issue 6 (15th March 2023) - Servadei, Francesca; Zoli, Luca; Galizia, Pietro; Melandri, Cesare; Failla, Simone; Sciti, Diletta
Abstract: Cf /ZrB2 –SiC composites were produced by water-based slurry impregnation followed by six cycles of polymer infiltration and pyrolysis at 1000 °C. Despite the mild temperature of pyrolysis, the flexural strength of this composite showed values in excess of 500 MPa even at elevated temperature, up to 1400 °C. The abrupt decay of strength at 1500 °C stimulated the need to investigate the effect of additional thermal treatments enabling the crystallization of the amorphous polymer derived SiC(O). Annealing treatments, carried out between 1400 °C and 1900 °C, led to evident microstructural changes that in turn affected the flexural strength measured both at room temperature and at 1500 °C. The microstructural evolution was carefully analysed and 1400 °C was identified as the best trade-off between temperature of the annealing treatment and mechanical performance. After annealing at 1400 °C, the strength of the composite at room temperature decreased from the initial 500 MPa for untreated samples to 300 MPa due to the creation of new porosity, but this strength value was then maintained up to 87% at 1500 °C. Annealing at higher temperatures were detrimental for microstructure and strength.